Análise quantitativa e temporal da área mata ciliar de trechos da Bacia do Rio Ivaí-Paraná - Brasil - Campos, Rafael Moreno (2013)
The way that the land was occupied and its uses by men have been shown to be incompatible with the fragile relationship among the physical and biotic components of the ecosystem. The anthropogenic action had already subtracted and made important ecosystems disappear. The process of occupation of the Paraná lands almost decimated the forests of this State which had 83.41% of its total area covered by forests and nowadays has approximately only 8% of forest coverage. The Northwest region is the critical one considering the forest coverage, since less than 1% of its area is covered by forests. This process of use and occupation of land was based on the horizontal expansion of the property and advanced over extreme ecological fragility of ecosystems, such as the Permanent Preservation Areas (PPA) - riparian forests. In this paper is analyzed the spatial and temporal vegetation occurring the edges of rivers in two areas of the Ivaí River Watershed (23º04' to 23º 20'S; 52º22' to 52º 27'W and 23º46' to 23º 55'S; 51º42' to 51º 58'), using aerial photographs from 1970 and satellite images from 2010. The polygons studied comprised a total area of 121,936.00ha and 46,453.00ha being quantified for the year 2010 an area of native vegetation on river edges 12,718.79ha and 4,964.69ha of which 5,138.22ha and 2,267.20ha are inserted in the buffer of 30 meters surrounding the river system of polygons 1 and 2, respectively, representing 95.12% and 87.98% of areas consistent with PPA. For the comparative evaluation of the situation of riparian forests on river edges between the years 1970 and 2010 was selected inside one of the polygons the Paranavaí stream and tributaries, where there was a substantial increase native vegetation on river edges between 1970 and 2010, which practically quadrupled. Has been registered in 1970 only 48.90% of the PPA had protective native vegetation (riparian forest). In 2010 reached a level very close to the legal requirements prevailing at that time (96.77% of the area covered by native vegetation PPA). The increase of native vegetation riparian registered in the study area may have been motivated by the conscientization process of landholders about the importance of PPA to improve local environmental quality, actions by governmental incentive programs for restoration of riparian areas, legal requirements imposed on landholders by fiscal agents, or all of these motivations together.